2007
DOI: 10.1111/j.1567-1364.2006.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin reduces ergosterol levels, inhibits growth and causes loss of mtDNA inCandida glabrata

Abstract: Statins are widely used for lowering cholesterol levels through their action on 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase. Yeasts use HMG-CoA reductase for the same enzymatic step as humans, but in yeasts the main end-product of the pathway is ergosterol rather than cholesterol. We considered that insights into the effects of statins in humans could be gained by examination of the effects of simvastatin on the petite-positive yeast Candida glabrata. Simvastatin was found to inhibit growth, and this wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 25 publications
2
70
0
Order By: Relevance
“…An inhibitor of squalene synthetase, an intermediate step in the cholesterol pathway, blocked staphyloxanthin production and attendant virulence in Staphylococcus aureus (43). Lovastatin-mediated growth inhibition has been reported for several pathogenic and nonpathogenic yeasts and one mold (31,39,44). For example, 100 M simvastatin or atorvastatin inhibited growth of four Candida species (C. albicans, tropicalis, glabrata, and parapsilosis) as well as Aspergillus fumigatus (36).…”
Section: Discussionmentioning
confidence: 99%
“…An inhibitor of squalene synthetase, an intermediate step in the cholesterol pathway, blocked staphyloxanthin production and attendant virulence in Staphylococcus aureus (43). Lovastatin-mediated growth inhibition has been reported for several pathogenic and nonpathogenic yeasts and one mold (31,39,44). For example, 100 M simvastatin or atorvastatin inhibited growth of four Candida species (C. albicans, tropicalis, glabrata, and parapsilosis) as well as Aspergillus fumigatus (36).…”
Section: Discussionmentioning
confidence: 99%
“…His screening showed that 17 genes involved in sterol uptake and/or transport are also involved in mitochondrial functions [32]. Mutants deficient in ergosterol biosynthesis showed swollen and clumped mitochondria [27]. All these point to a significant interconnection between the mevalonate pathway and mtDNA maintenance in the yeast cell.…”
Section: Statin Effects On Yeast Mitochondrial Functionsmentioning
confidence: 97%
“…Furthermore, unlike regular spontaneous petites that undergo specific deletions in their mitochondrial genome and amplify the remaining DNA (so-called ρ − petites), statin-induced petites are totally devoid of mtDNA and are designated ρ o . DAPI (4 ,6-diamidino-2-phenylindole) staining of cellular DNA of petites showed that only nuclear DNA was present in such cells (see Figures 2B and 2C) [27].…”
Section: Statin Effects On Yeast Mitochondrial Functionsmentioning
confidence: 98%
See 2 more Smart Citations